Effect of the jigsaw technique as a cooperative learning approach on motivation and job performance of community health workers: A quasi-experimental study - Sareh Shakerian; Leila Hassan Abadi (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: In Iran, community health workers (CHWs) are native and are only employed in the health-care system. Therefore, the training and empowerment of these staff are essential. The present study was aimed to develop cooperative learning techniques in CHWs to improve both cognitive and noncognitive aspects such as accountability and other social skills in learners. METHODOLOGY: This study employed a quasi-experimental pre- and post-test design with a control group that was conducted in Kangavar City, Iran, in 2019. Forty-four CHWs were selected using a two-stage cluster sampling, of whom 22 were randomly assigned to the experimental group where the jigsaw technique was applied and the rest to the control group where the lecture method was applied. The aim was to identify job performance and motivation among the CHWs after instruction and compare the two groups. Pre- and posttests were applied to the groups before and after an in-service training course using valid questionnaires. Data analysis was performed on both descriptive and inferential statistics such as mean and standard deviation, paired t-test, and covariance analysis with the confidence level of 95%. RESULTS: The findings showed that the intervention significantly increased the mean score of motivation and performance in the experimental group. Covariance analysis with the removal of the pretest effect was also statistically significant (P = 0.01). Moreover, the MANCOVA test showed the jigsaw technique effect considering motivation and performance with a confidence level of 95%. CONCLUSION: Given the well-known effect of cooperative learning techniques and since CHWs have multi roles and tasks, it is necessary to use such techniques so that they can be accountable for developing health indicators in local areas.